The role of macroeconomic and financial factors in bond market development in selected countries - Aman, Ameenullah; Isa, Mohamad Yazid; Mohamed Naim, Asmadi (SAGE Journal, 2020)
Both developed and developing economies have showed serious interest in the development of domestic and regional bond markets. This interest was motivated by the recurrent events of economic crises, due to the over-reliance on the banking system. Therefore, this study investigates the macroeconomic and financial determinants of a bond market development, since the economic and financial environments play a primary role in the development of any financial market. Panel data analysis is employed to investigate the potential relationships. Results identify that financial system and most of the macroeconomic factors are positively associated with a bond market development. However, the stage of economic development is negatively related to bonds. Hence, policymakers need to strengthen and use existing financial system and economic variables to provide reasonable support to the development of bond markets. This study empirically analyses some unexplored theoretical relationships with respect to a bond market.